Risk stratification for the primary prevention of arrhythmic sudden cardiac death in post‐infarction patients: Part II: Cardiac magnetic resonance and electrophysiological study. Trials connecting the risk stratification approaches with the ICDs. The unexplored new eras of the stable patients with preserved ejection fraction and the patients within the early post‐myocardial infarction period. Issue 3 (September 2016) - Arsenos, P.; Sideris, S.; Gatzoulis, K. A.
Abstract: Current trends on Sudden Cardiac Death (SCD) Risk Stratification complementary to the conventional markers that were presented in Part I, are Cardiac Magnetic Resonance that detects and quantifies the post‐infarct tissue heterogeneity and the invasive method of Programmed Ventricular Stimulation on Electrophysiological study that reveals the vulnerable and inducible myocardial substrate. While the first generation of Risk Stratification trials examined one simple prognostic marker each time, the second generation of trials investigated in past combinations of SCD prediction markers and prognostic models reflecting different arrhythmogenesis mechanisms. The third generation of trials currently utilizes Risk Stratification strategies to indentify high‐risk patients before an ICD prophylactic implantation connecting the Risk Stratification process with the ICD therapy. Intensive research on SCD is also nowadays directed to the unexplored era of patients with a Preserved Ejection Fraction and to the era of early post‐myocardial infarction period. Both these subgroup patients are not protected by the current ICDs implantation guidelines because of gap in evidence. Research is going to fill in this gap. Answer questions and earn CME :https://wileyhealthlearning.com/Activity2/4469470/Activity.aspx